The price of peace true accounts of the Japanese occupation - Foong, Choon Hon (Asiapac Books, 2002)
One day in February 1942, the people of Singapore were rudely awakened to the fact that the peace and freedom they enjoyed had been taken away. Japan, a strong military power, had invaded their land and began a reign of terror that lasted a nighmarish three and a half year. All expressions of human rights were lost overnight.